891 Improvement in VTE Prophylaxis and Hospital Admission Time for Colorectal Cancer Patients Following the Introduction of an Enhanced Recover After Surgery (ERAS) Nurse. (19th August 2022) - Zhu, XM; Cribb, E; Smith, J; Ashton, G; Pawa, N
Abstract: Aim: Patients undergoing abdominopelvic surgery at high risk of developing VTE and NICE guidelines mandate a 28-day course of post-operative pharmacological prophylaxis for these patients. We completed a closed loop re-audit to examine the local trust adherence to national guidelines. Method: A closed loop re-audit was performed to check for appropriate VTE prescription. 62 patients undergoing elective surgery for colorectal cancer were identified from May 2017 to April 2018. An ERAS nurse was appointed following the initial audit and subsequent data was collected on a cohort of 80 eligible patients from April 2021 to October 2021. Results: Previous compliance against national guidance set by NICE was 32% for patients screened from May 2017 to April 2018. There was a significant improvement to a 74% compliance rate following the introduction of an ERAS nurse. The appointment of the ERAS nurses also resulted in a reduction in postoperative hospital stay of 1.2 days. Conclusions: A significant improvement in appropriate VTE prophylaxis was provided to patients following the introduction of a dedicated ERAS nurse. In addition, patients had a mean reduction in hospital stay length. Several points for future investigation based on findings: identification of cause behind missed prescriptions, patient education on self-administration of LMWH on discharge when applicable, and whether any VTE related complications occurred in either cohort.